2017
DOI: 10.1016/j.yebeh.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine serum levels: Ceiling effect in people with epilepsy in remission?

Abstract: An association between lamotrigine serum levels and seizure response can be observed. This suggests the existence of a ceiling level, above which remission is unlikely and should prompt antiepileptic medication switch rather than further up-titration of lamotrigine in drug-naïve patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Fourthly, the relationship between blood or brain exposure and therapeutic efficacy might display important between-patient pharmacodynamic variability: a similar observation was done for lacosamide in the same clinical setting (Perrenoud et al, 2017). Making a parallel with chronic epilepsy in an outpatient setting, most of the medication effect in responders is usually obtained at low dosage, and increasing doses seem to bring little additional benefit in terms of remission (D'Anto et al, 2017;Poolos et al, 2017) Our response rate to LEV was 34%, lower than previous studies with similar dosages that reported rates of 68.5% in 204 episodes (Yasiry and Shorvon, 2014), or 65.4% in 156 episodes (Trinka and Dobesberger, 2009). Direct comparisons are however difficult, because the definition of clinical response was not uniform across those studies and most of them, as ours, had a retrospective design making them prone to inclusion bias.…”
Section: Discussionmentioning
confidence: 87%
“…Fourthly, the relationship between blood or brain exposure and therapeutic efficacy might display important between-patient pharmacodynamic variability: a similar observation was done for lacosamide in the same clinical setting (Perrenoud et al, 2017). Making a parallel with chronic epilepsy in an outpatient setting, most of the medication effect in responders is usually obtained at low dosage, and increasing doses seem to bring little additional benefit in terms of remission (D'Anto et al, 2017;Poolos et al, 2017) Our response rate to LEV was 34%, lower than previous studies with similar dosages that reported rates of 68.5% in 204 episodes (Yasiry and Shorvon, 2014), or 65.4% in 156 episodes (Trinka and Dobesberger, 2009). Direct comparisons are however difficult, because the definition of clinical response was not uniform across those studies and most of them, as ours, had a retrospective design making them prone to inclusion bias.…”
Section: Discussionmentioning
confidence: 87%
“…The main mechanism of oxcarbazepine is inhibiting the repeated discharge of neurons by blocking voltage-dependent sodium ion channels in brain cells (21). The main mechanism of lamotrigine is inhibiting voltage-dependent calcium and sodium channels to control the temperature of the presynaptic membrane and inhibit the release of neurotransmitters, ultimately reducing abnormal discharge of neurons (22). The HAMD and MADRS scores of patients from both groups before and after treatment were also compared.…”
Section: Discussionmentioning
confidence: 99%
“…Their pharmacokinetic characteristics make newer generation ASM’s potentially good candidates for TDM 10 . Recently, we reported that maximal efficacy of LTG could be reached at blood levels below 8.2 mg/L, representing a ceiling concentration associated with seizure freedom in that retrospective cohort 11 …”
Section: Introductionmentioning
confidence: 94%